The Immunomodulatory Functions of BTK Inhibition in the Central Nervous System - Cao T; Wang Z; Zhu X (Dove Medical Press, 2022)
Tingyu Cao,1 Zengguang Wang,2 Xiaodong Zhu1 1Department of Neurology, Tianjin Neurological Institute, Tianjin Medical University General Hospital, Tianjin, People's Republic of China; 2Department of Neurosurgery, Tianjin Neurological Institute, Tianjin Medical University General Hospital, Tianjin, People's Republic of ChinaCorrespondence: Xiaodong Zhu, Department of Neurology, Tianjin Neurological Institute, Tianjin Medical University General Hospital, Tianjin, People's Republic of China, Tel +86 13312142939, Email zxd3516@tmu.edu.cn Zengguang Wang, Department of Neurosurgery, Tianjin Neurological Institute, Tianjin Medical University General Hospital, Tianjin, People's Republic of China, Email wangzengguang@tmu.edu.cnAbstract: Bruton's tyrosine kinase (BTK) is a central signaling node in B cells. BTK inhibition has witnessed great success in the treatment of B-cell malignancies. Additionally, in the immune system, BTK is also a prominent component linking a wide variety of immune-related pathways. Therefore, more and more studies attempting to dissect the role of BTK in autoimmune and inflammation progression have emerged in recent years. In particular, BTK expression was also found to be elevated within the central nervous system (CNS) during neuroinflammation. BTK inhibitors are capable of crossing the blood-brain barrier rapidly to modulate B cell functions, attenuate microglial activities and affect NLRP3 inflammasome pathways within the CNS to improve the outcome of diseases. Thus, BTK inhibition appears to be a promising approach to modulate dysregulated inflammation in the CNS and alleviate destruction caused by excessive inflammatory responses. This review will summarize the immunomodulatory mechanisms in which BTK is involved in the development of neurological diseases and discuss the therapeutic potential of BTK inhibition for the treatment of neuroinflammatory pathology.Keywords: BTK, BTK inhibition, BTK inhibitors, neuroinflammation